Male Gender Is Associated with Lymph Node Metastasis but Not with Recurrence in Papillary Thyroid Carcinoma - Jiang Zhu; Rui Huang; Ping Yu; Haoyu Ren; Xinliang Su (International Journal of Endocrinology)
Background. The incidence of papillary thyroid carcinoma (PTC) is higher in females than in males, but it remains unclear whether gender is associated with the aggressiveness of this disease. We aimed to clarify the influence of gender on the risk of developing lymph node metastasis (LNM) and on the prognosis of PTC patients. Study Design. Retrospective cohort study. Setting. Academic tertiary care center. Methods. Clinical data of PTC patients who were admitted to the Department of Endocrine and Breast Surgery, the First Affiliated Hospital of Chongqing Medical University, between January 2013 and December 2018 were retrospectively reviewed. The differences in clinical features and outcomes between female and male patients were compared. Univariate and multivariate logistic regression analyses were conducted to assess the impact of gender on LNM. Kaplan–Meier curves were used to estimate recurrence-free survival (RFS). Results. A total of consecutive 2536 patients were enrolled in this study. Males accounted for 25.2% (639 cases) of all patients. Central lymph node metastasis (CLNM) and lateral lymph node metastasis (LLNM) rates were 52.5% (1346/2536) and 22.0% (558/2536), respectively. Male presented with higher LNM rates than female patients (65.7% vs. 51.2%; P<0.001). Male gender was independently associated with LNM (OR = 1.93, 95% CI: 1.59–2.35; P<0.001). After full adjustment, male gender still remained significantly associated with CLNM in all subgroups; however, subgroup analyses indicated no significant relationship between gender and LLNM. In addition, after a median follow-up period of 30 months, no significant difference was found in RFS between female and male patients (P=0.15). Conclusions. This observational cohort study revealed that male gender was significantly associated with CLNM; whereas, LLNM was not different between female and male PTC patients in southwestern China. Moreover, currently, there is insufficient evidence to justify that male gender is an independent prognostic factor for recurrence.